Elevated Rates of Ventilator-Associated Pneumonia and COVID-19 Associated Pulmonary Aspergillosis in Critically Ill Patients with SARS-CoV2 Infection in the Second Wave: A Retrospective Chart Review - Sean Boyd; Kai Sheng Loh; Jessie Lynch; Dhari Alrashed; Saad Muzzammil; Hannah Marsh; Mustafa Masoud; Salman Bin Ihsan; Ignacio Martin-Loeches (MDPI AG, 2022)
Due to multiple risk factors, the rate of ventilator-associated pneumonia in critically ill COVID-19 patients has been reported in a range of 7.6% to 86%. The rate of invasive pulmonary aspergillosis in this cohort has been reported at 4% to 30%. We undertook a retrospective chart review of 276 patients who were admitted to intensive care in a large university hospital. The period studied included patients from 23 February 2014 to 12 May 2021. Four groups were collected: COVID-19 Wave 1, COVID-19 Wave 2, influenza, and community-acquired pneumonia. Clinical characteristics, outcomes, and microbiological cultures were recorded. The incidence of ventilator-associated pneumonia in COVID-19 Wave 1, COVID-19 Wave 2, influenza, and community-acquired pneumonia was 5.45%, 27.40%, 16.67%, and 3.41%, respectively (p < 0.001). The rate of invasive pulmonary aspergillosis was 0%, 9.59%, 13.33%, and 6.82%, respectively (p < 0.001). A significantly elevated rate of ventilator-associated pneumonia and invasive pulmonary aspergillosis was noted in the second wave of COVID-19 when compared to the first. This was accompanied by an increase in the mortality rate. Increased steroid use was an independent risk factor for ventilator-associated pneumonia and invasive pulmonary aspergillosis across all four groups. Despite an increased understanding of this disease, no clinical trials have shown any promising therapeutic options at present.